A Theoretical Calculation of Electrical Energy Production from the Incineration of Baghdad Municipal Solid Wastes (Journal of Engineering, 2024)
A theoretical investigation study was carried out to determine the requirements of establishing a steam power plant by incinerating municipal solid wastes generated from the city of Baghdad. Survey data the generated quantities of municipal solid wastes from both Al-Karth and Al-Rusafa sectors of the city were utilized to predict the theoretical possible energy production that can be obtained from the incineration of this waste under controlled parameters. Results reviled that the high heating value of Baghdad’s municipal solid wastes is of about (12.789 MJ/kg) and the possible electrical energy production in the steam power plants in Al-Karth and Al-Rusafa are (119.287 MW, 203.917 MW) respectively using a steam turbine of efficiency (25%). Resulted emissions of CO2 gases are estimated to be 4209.995 ton/day. So the emission of CO2 is the main problem of this method because of its effect on global warming but it is less effect on environment from Methane, Sulphur Oxides and Nitrogen Oxides. The quantity of plastic wastes in Municipal Solid Wastes is important in increasing their average high heating value.